Modeling and characterization of a new three-stage quadruple pass EDFA - Naji, Ahmed Wathik; Akhter, Fowzia; Ibrahimy, Muhammad Ibn; Siddiquei, Hasin Reza (2012)
A new three-stage quadruple pass (QP) EDFA is presented in this paper. The mathematical models for designing this proposed EDFA are developed. In the mathematical models, the effects of amplified spontaneous emission (ASE) of prior stages are included. Performance analysis of this QP EDFA is carried out with the variation of input pump power ratio and signal power. Change in Erbium ions concentration in energy level 1 and energy level 2 with the variation of fiber length is also analyzed to determine optimum fiber length. From the obtained results the optimum design parameters (pump power, signal power, fiber length) are recommended for practical implementation.